2022
DOI: 10.3390/ph15101190
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Quantitative Relationship and Mechanism of Plant Flavonoids to Gram-Positive Bacteria

Abstract: Antimicrobial resistance (AMR) poses a serious threat to human health, and new antimicrobial agents are desperately needed. Plant flavonoids are increasingly being paid attention to for their antibacterial activities, for the enhancing of the antibacterial activity of antimicrobials, and for the reversing of AMR. To obtain more scientific and reliable equations, another two regression equations, between the minimum inhibitory concentration (MIC) (y) and the lipophilicity parameter ACD/LogP or LogD7.40 (x), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 44 publications
5
28
0
Order By: Relevance
“…This confirmed again that the lipophilicity is a key factor of plant flavonoids against gram-positive bacteria. Another, according to the rules that the predicted MICs ranged from 1/4× to 4× the determined ones were acceptable [14,15] and those less than 1/8× or more than 8× the determined ones were completely unacceptable, the calculated MIC values of only one plant flavonoid as echinatin was unacceptable, and which once again confirmed the efficiency of equation ( 1) for predicting the MICs of plant flavonoids against gram-positive bacteria.…”
Section: Calculated and Tested Minimum Inhibitory Concentrations (Mics)supporting
confidence: 52%
See 3 more Smart Citations
“…This confirmed again that the lipophilicity is a key factor of plant flavonoids against gram-positive bacteria. Another, according to the rules that the predicted MICs ranged from 1/4× to 4× the determined ones were acceptable [14,15] and those less than 1/8× or more than 8× the determined ones were completely unacceptable, the calculated MIC values of only one plant flavonoid as echinatin was unacceptable, and which once again confirmed the efficiency of equation ( 1) for predicting the MICs of plant flavonoids against gram-positive bacteria.…”
Section: Calculated and Tested Minimum Inhibitory Concentrations (Mics)supporting
confidence: 52%
“…Twelve plant flavonoids (Figure 1), with seven structural subtypes including dihydroflavones, flavonols, flavones, isoflavones, chalcones, flavanes and xanthones, were selected for verifying the inference that the quinone pool is a key target of plant flavonoids inhibiting gram-positive bacteria. Their average MICs (or MIC90s) against gram-positive such as S. aureus, S. epidermidis and Bacillus subtilis were calculated according to equation (1) in section 4.3 [15], and the results (Table 1) showed that they had different degrees of inhibitory activities and can be used for further screening to obtain required flavonoids with different antibacterial activities.…”
Section: Calculated and Tested Minimum Inhibitory Concentrations (Mics)mentioning
confidence: 99%
See 2 more Smart Citations
“…Prenylation facilitates lipophilicity and increases the efficacy of interaction with membrane and target proteins ( Kushwaha et al, 2019 ). For the antimicrobial activity of flavonoids to Gram-positive bacteria, lipophilicity is a key factor ( Yuan et al, 2022 ). Moreover, prenylated flavonoids play an important role in key signaling pathways in the body ( Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%